Profiling rural tourists in Semporna, Sabah, Malaysia - Chia, Kei Wei; Shuib, Ahmad; Mohammad Afandi, Syamsul Herman; Ramachandran, Sridar (2014)
Rural tourism is importance in many countries and regions due to its ability to generate income for government and local communities. Understand who the tourists are and the motivation of their visit is important for tourism stakeholders to boost the local tourism development and economy through marketing. Thus, this study aims to profile rural tourist’s information regarding trip related and socio demographic information to identify key market segments of tourists. This result provides detailed information on the tourist profile in Semporna based on 381 face-to face interviews. The findings indicate that tourists visit Semporna for scuba diving and holiday and majority of them are first timer travel by bus or taxi. The average length of stay is 4 nights and budget lodging is the preferred type of accommodation. In term of companion, respondents prefer to travel with friends and spouse. There are more female than male age between 19-40 and most hold bachelor degree or higher. More than half of the respondents purchase a package tour. This study is expected to provide some contributions for tourism stakeholders, including policy makers, tour operators, investors, and destination management organizations.